Pengaruh Current Ratio, Debt to Equity Ratio, Total Asset Turnover dan Return On Equity terhadap Harga Saham : (Studi Empiris Pada Perusahaan Publik yang Tergabung dalam Jakarta Islamic Index di Bursa Efek Indonesia Periode 2019-2023) - Iftitah Mutiara Sudiro; Retno Fuji Oktaviani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine the influence of the Current Ratio, Debt To Equity Ratio, Total Asset Turnover and Return On Equity on Share Prices in Jakarta Islamic Index Public Companies on the Indonesia Stock Exchange (BEI) for the 2019-2023 period. This research uses quantitative research methods with a population and sample from the Jakarta Islamic Index Public Companies on the Indonesia Stock Exchange for the 2019-2023 period. There are 16 companies that are the object of this research, determined using certain criteria. The analytical methods in this research consist of the classic assumption test, correlation coefficient analysis test, multiple linear regression analysis test, determination analysis test (R2), t test and F test. Meanwhile, the data analysis method used is multiple linear regression with a significance value of 0.05 using Static Product and Service Solution (SPSS) Version 22.0. The results of this research show that the Current Ratio partially influences and significant share prices, while the Debt To Equity Ratio, Total Asset Turnover and Return On Equity have no influence and not significcant on share prices. Simultaneously Current Ratio, Debt To Equity Ratio, Total Asset Turnover and Return On Equity influence share prices.